Blast-Induced Damage on Millisecond Blasting Model Test with Multicircle Vertical Blastholes. (21st May 2015) - Ma, Qin-yong; Yuan, Pu; Zhang, Jing-shuang; Ma, Rui-qiu; Han, Bo
Abstract : To investigate the blast-induced damage effect on surrounding rock in vertical shaft excavation, 4 kinds of millisecond blasting model tests with three-circle blastholes were designed and carried out with excavation blasting in vertical shaft as the background. The longitudinal wave velocity on the side of concrete model was also measured before and after blasting. Then blast damage factor was then calculated by measuring longitudinal wave velocity before and after blasting. The test results show that the blast-induced damage factor attenuated gradually with the centre of three-circle blastholes as centre. With the threshold value of 0.19 for blast-induced damage factor, blast-induced damage zones for 4 kinds of model tests are described and there is an inverted cone blast-induced damage zone in concrete model. And analyses of cutting effect and blast-induced damage zone indicate that in order to minimize the blast-induced damage effect and ensure the cutting effect the reasonable blasting scheme for three-circle blastholes is the inner two-circle blastholes initiated simultaneously and the outer third circle blastholes initiated in a 25 ms delay.